2019
DOI: 10.1002/jcp.29048
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0039411 promotes tumorigenesis and progression of papillary thyroid cancer by miR‐1179/ABCA9 and miR‐1205/MTA1 signaling pathways

Abstract: Papillary thyroid cancer (PTC) is a common malignancy in endocrine system worldwide.Increasing evidence has shown that dysregulation of circular RNAs (circRNAs) could contribute to PTC tumorigenesis. The aims of this project are to investigate the potential role and molecular mechanism of hsa_circ_0039411 in PTC. In the project, RT-qPCR was performed to measure the expression profile of hsa_circ_0039411 in PTC tissues and cells.Cell counting kit-8, clonogenic, flow cytometric, and transwell experiments were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…For instance, a previous study published that the tumor suppressor function of miR-1179 was confiscated by circ_0000735 during the development of non-small cell lung cancer [51]. A similar experiment confirmed that the inhibitory effect of miR-1179 on thyroid cancer was sponged by circ_0039411 during the pathological process [52]. Another study pointed out that circ_0003645 improved cell aggressiveness through sponging miR-1179 [53].…”
Section: Discussionmentioning
confidence: 74%
“…For instance, a previous study published that the tumor suppressor function of miR-1179 was confiscated by circ_0000735 during the development of non-small cell lung cancer [51]. A similar experiment confirmed that the inhibitory effect of miR-1179 on thyroid cancer was sponged by circ_0039411 during the pathological process [52]. Another study pointed out that circ_0003645 improved cell aggressiveness through sponging miR-1179 [53].…”
Section: Discussionmentioning
confidence: 74%
“…9 In TC, the roles of circ_0039411 and circ_0025033 had been elucidated, both of which could promote the progression of TC. 10,11 Circ_0058124 is a newly discovered circRNA differentially expressed in TC and has been proved to be associated with the poor prognosis of patients. 12 However, the role and mechanism of TC should be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a previous study published that the tumor suppressor function of miR-1179 was con scated by circ_0000735 during the development of non-small cell lung cancer [51]. A similar experiment con rmed that the inhibitory effect of miR-1179 on thyroid cancer was sponged by circ_0039411 during the pathological process [52]. Another study pointed out that circ_0003645 improved cell aggressiveness through sponging miR-1179 [53].…”
Section: Discussionmentioning
confidence: 91%